Miscellaneous Perianal Afflictions - Hagerman, Gonzalo F.; Silva-Velazco, Jorge; Molina-Lopez, Juan Francisco (Clinics in Colon and Rectal Surgery, 2019)
This article provides an overview of hidradenitis suppurativa, lichen planus, lichen sclerosis, calcinosis cuti, pyogenic granuloma, intertrigo, and seborrheic keratosis. This article also focuses on recognition and management of these pleomorphic afflictions of the perianal region.
Keywords: hidradenitis suppurativa; lichen planus; lichen sclerosis; calcinosis cuti; pyogenic granuloma; intertrigo and seborrheic keratosis